2022
DOI: 10.1111/evj.13575
|View full text |Cite
|
Sign up to set email alerts
|

Plantar osteochondral fragments in young Standardbreds are associated with minimal joint inflammation at the time of surgical removal

Abstract: Background: Plantar osteochondral fragments (POF) are common but their effect on joint health of young Standardbreds in race training is largely unknown. Objectives: Evaluate the inflammatory effects of POF in metatarsophalangeal joints of young Standardbreds as a step towards developing evidence-based recommendations for surgical removal. Study design: Cohort study. Methods: Forty-nine Standardbred horses (age 11-33 months) presented for surgical removal of POF from 56 metatarsophalangeal joints. Synovial tis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(11 citation statements)
references
References 30 publications
3
8
0
Order By: Relevance
“…However, this also included older horses and other breeds than Standardbred trotters. Since age was found to be associated with cartilage injury, this might explain why cartilage lesions were more commonly found in the current study than what was reported by McCoy et al 45 It has been previously reported that Warmblood stallions with OCD of the sagittal ridge of the distal MC3/MT3 will likely have poorer future jumping performance than nonaffected horses 3 . However, the prognosis for athletic function is favourable for Types II (fragment associated to OCD defect) and III (OCD defect or flattening with or without fragmentation and one or more loose fragments) lesions with timely intervention, hindlimb lesions and when no degenerative changes are present within the joint 8,46 .…”
Section: Discussionsupporting
confidence: 41%
See 4 more Smart Citations
“…However, this also included older horses and other breeds than Standardbred trotters. Since age was found to be associated with cartilage injury, this might explain why cartilage lesions were more commonly found in the current study than what was reported by McCoy et al 45 It has been previously reported that Warmblood stallions with OCD of the sagittal ridge of the distal MC3/MT3 will likely have poorer future jumping performance than nonaffected horses 3 . However, the prognosis for athletic function is favourable for Types II (fragment associated to OCD defect) and III (OCD defect or flattening with or without fragmentation and one or more loose fragments) lesions with timely intervention, hindlimb lesions and when no degenerative changes are present within the joint 8,46 .…”
Section: Discussionsupporting
confidence: 41%
“…In the current study, POF were also not as likely to be associated with cartilage lesions as dorsal fragments. This might be because POF, in contrast to other fragments, are often well‐embedded in the joint and more stable due to attachment of the distal sesamoidean ligaments 45 . In a recent study by McCoy et al, 45 arthroscopic images of 56 joints of 49 young Standardbred trotters with POF were retrospectively evaluated for joint abnormalities.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations